Staying alive: A 21st century agenda for mental health, child protection and forensic services. Issue 1 (1st February 2021) - Crittenden, Patricia M; Landini, Andrea; Spieker, Susan J
Mental health treatment, child protection and forensic services for criminality need major reorganisation in conceptualisation and service provision. This need results from the failure of current diagnostic methods, administrative organisations and treatment approaches to reduce the prevalence of mental illness, child maltreatment or criminal behaviour. We propose that defining these problems as individual deficits and responding to them by category of harm (to self, progeny and others, respectively) stands in the way of effective prevention and treatment. We address four topics: (1) the common basis of all of these problems in unprotected and uncomforted exposure to danger, (2) the developmental process of psychological maladaptation that occurs interpersonally in endangered families, (3) the behavioural expression of psychological development as protective strategies that can be adaptive or maladaptive, depending upon the context in which they are used, and (4) proposals for systemic change that could improve prevention and treatment. These proposals include using functional formulations to guide treatment planning, single portal entry to assessment and services, integrated universal transdisciplinary training followed by specialisation for all mental health professionals, delivering customised treatment through transitional attachment relationships and consolidating disparate disciplines in 'departments of human adaptation'.